Synthesis, Characterization, and Applications of Zwitterions Containing a Carbanion Moiety1. Issue 5 (13th December 2012) - Yanai, Hikaru; Yoshino, Tasuku; Fujita, Masaya; Fukaya, Haruhiko; Kotani, Akira; Kusu, Fumiyo; Taguchi, Takeo
<x xml:space="preserve">Abstract</x> A trifle of triflyl: N‐substituted anilines react with 1, 1, 3, 3‐tetrakis(triflyl)propane to give a 2, 2‐bis(triflyl)ethyl group at the para position of the ring. The product is a zwitterion with a carbanion and an ammonium moiety, and can be used as an acid catalyst for organic reactions (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>